CRACM1 is a plasma membrane protein essential for store-operated Ca2+ entry. - Vig, M.; Peinelt, C.; Beck, A.; Koomoa, D.L.; Rabah, D.; Koblan-Huberson, M.; Kraft, S.; Turner, H.; Fleig, A.; Penner, R.; Kinet, J.P. (Science, 2006)
Store-operated Ca2+ entry is mediated by Ca2+ release-activated Ca2+ (CRAC) channels following Ca2+ release from intracellular stores. We performed a genome-wide RNA interference (RNAi) screen in Drosophila cells to identify proteins that inhibit store-operated Ca2+ influx. A secondary patch-clamp screen identified CRACM1 and CRACM2 (CRAC modulators 1 and 2) as modulators of Drosophila CRAC currents. We characterized the human ortholog of CRACM1, a plasma membrane-resident protein encoded by gene FLJ14466. Although overexpression of CRACM1 did not affect CRAC currents, RNAi-mediated knockdown disrupted its activation. CRACM1 could be the CRAC channel itself, a subunit of it, or a component of the CRAC signaling machinery.